Learning from Danish counter-piracy off the coast of Somalia - Jessica Larsen; Christine Nissen (Danish Institute for International Studies (DIIS), 2017)
Since the mid-2000s, piracy off the coast of Somalia has posed a serious threat to international shipping and the safety of seafarers. As a seafaring nation, combating Somali piracy quickly became an important security and foreign policy priority for Denmark. This report documents Denmark's recent role in international counterpiracy off the coast of Somalia and examines the challenges and opportunities posed by Danish involvement. The reports offers central points for policy-makers to take into account when planning future participation in international maritime security operations, including other forms of maritime crime such as drug- and weapon-smuggling in the Indian Ocean and human trafficking in the Mediterranean. The report identifies four areas in particular in which Denmark may contribute to maritime security. These areas are aligned with Danish capabilities and interests, as well as critical gaps in existing international engagement. They are: * continuing support to the international agenda of multilateralism in maritime security; * emphasising long-term capacity-building of regional maritime security capabilities; * accounting for local conditions in policy planning regarding cooperation with regional states; * strengthening Danish maritime security policy by systematically evaluating civil-military cooperation.
Keywords: 300